Hubungan Lama Penggunaan Kontrasepsi IUD Dengan Kejadian Anemia Pada PesertaKontrasepsi IUD Di Desa Gayaman Kecamatan Mojoanyar Kabupaten Mojokerto - Khusuiyati, Etik; Prasastia Lukita Dewi, Catur (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstrakContraceptive IUD is a contraceptive that is implanted in the uterus. One of the complications of IUD contraceptives are menstrual bleeding in large quantities. Heavy bleeding during menstruation or in between that allows the cause of anemia. The purpose of this study was to determine the relationship between the old lUD contraceptive use with the incidence of anemia among participants in IUD contraception in Gayaman Village Mojoanyar District Mojokerto Regency. This research method uses analytic correlation design using cross-sectional approach. The population in this study were all participants in IUD contraception Gayaman Village Mojoanyar District Mojokerto Regency in June 2016. Total population as many as 48 people. Sampling used is total sampling. The results showed that the highest long IUDcontraceptive use is >3-4 years (25%) and 14-5 years (25%), the incidence of anemia in half JUD contraceptionparticipants experienced mild anemia (48%). Analysis of the data used is to use a crosstab so that it is known that there is a long association with the IUD contraceptive use on the incidence of anemia in the village of IUD contraception participants Gayaman Village Mojoanyar District Mojokerto Regency. Midwives should improve the ability and professional attitude in managing obstetric care in family planning, especially in participants IUD contraception, providing comprehensive family planning services by providing counseling on contraceptive JUD side effects and how to overcome them.Keywords: Time use, contraceptive IUD, anemic